Antibacterial and antioxidative activity tests on extract of siuri (Koordersiodendron pinnatum (Blanco) Merr.) cortex - Praptiwi .; Mindarti Harapini (Indonesian Journal of Pharmacy, 2004)
The aim of the study was to determine the in-vitro antibacterial and antioxidative activities of siuri (Koordersiodendron pinnatum) bark extract. Ethanolic, hexane, chloroform and ethyl acetate extracts were tested for antibacterial activity against 7 bacteria isolates which were 4 Gram Positive bacteria (Staphylococcus aureus, S. epidermidis, Streptococcus agalactiae, Corynebacterium sp.) and 3 Gram Negative bacteria (Salmonella enteritidis, Eschericia coli, Pseudomonas aeruginosa). Extract concentrations used were : 50, 25, 12.5 and 6.75%. The experiments were conducted in triplicate in Mueller Hinton Agar (MHA). Antioxidative test was performed at the concentration of 1, 5 and 10% with aquadest as a negative control and α-tocopherol as positive control. The results showed that the ethyl acetate extract inhibited the growth of 7 bacteria tested, and the growth inhibition area on Gram negative bacteria was wider than that of 10 units of penicillin. Peroxide value of ethanol extract (111.29) was lower than that of  α-tocopherol. Increasing extract concentration reduced the absorbance value.Key words : Koordersiodendron pinnatum, antibacteria, antioxidant.